Carnosic Acid Mitigates Early Brain Injury After Subarachnoid Hemorrhage: Possible Involvement of the SIRT1/p66shc Signaling Pathway - Teng, Lingfang; Fan, Linfeng; Peng, Yujiang; He, Xijun; Chen, Huihui; Duan, Hongyu; Yang, Fan; Lin, Da; Lin, Zheng; Li, Huiyong; Shao, Bo (Frontiers in Neuroscience, 2019)
Carnosic acid (CA) has been reported to exhibit a variety of bioactivities including antioxidation, neuroprotection, and anti-inflammation; however, the impact of CA on subarachnoid hemorrhage (SAH) has never been elucidated. The current study was undertaken to explore the role of CA in early brain injury (EBI) secondary to SAH and the underlying mechanisms. Adult male Sprague-Dawley rats were perforated to mimic a clinical aneurysm with SAH. CA or vehicle was administered intravenously immediately after the SAH occurred. Mortality, SAH grade, neurologic function scores, brain water content, Evans blue extravasation, and the levels of reactive oxygen species (ROS) levels in the ipsilateral cortex were determined 24h after the SAH occurred. Western blot, immunofluorescence, Fluoro-Jade C (FJC) and TUNEL staining were also performed. Our results showed that CA decreased ROS levels, alleviated brain edema and blood-brain barrier permeability, reduced neuronal cell death and promoted neurologic function improvement. To probe into the potential mechanisms. We showed that CA increased SIRT1, MnSOD and Bcl-2 expression, as well as decreased p66shc, Bax, and cleaved caspase-3 expression. Interestingly, sirtinol, a selective inhibitor of SIRT1, abolished the anti-apoptotic effects of CA. Taken together, these data revealed that CA has a neuroprotective role in EBI secondary to SAH. The potential mechanism may involve suppression of neuronal apoptosis through the SIRT1/p66shc signaling pathway. CA may provide a promising therapeutic regimen for management of SAH.